Transcriptome analysis of Sf9 insect cells during production of recombinant Adeno‐associated virus - Virgolini, Nikolaus (2023)
The insect cell-baculovirus expression vector system (IC-BEVS) has emerged as an alternative time- and cost-efficient production platform for recombinant Adeno-associated virus (AAV) for gene therapy. However, a better understanding of the underlying biological mechanisms of IC-BEVS is fundamental to further optimize this expression system toward increased product titer and quality. Here, gene expression of Sf9 insect cells producing recombinant AAV through a dual baculovirus expression system, with low multiplicity of infection (MOI), was profiled by RNA-seq. An 8-fold increase in reads mapping to either baculovirus or AAV transgene sequences was observed between 24 and 48 h post-infection (hpi), confirming a take-over of the host cell transcriptome by the baculovirus. A total of 336 and 4784 genes were identified as differentially expressed at 24 hpi (vs non-infected cells) and at 48 hpi (vs. infected cells at 24 hpi), respectively, including dronc, birc5/iap5, and prp1. Functional annotation found biological processes such as cell cycle, cell growth, protein folding, and cellular amino acid metabolic processes enriched along infection. This work uncovers transcriptional changes in Sf9 in response to baculovirus infection, which provide new insights into cell and/or metabolic engineering targets that can be leveraged for rational bioprocess engineering of IC-BEVS for AAV production.